Похищение блудного попугая. Мультипликационные истории - Курляндский А. Е. (Страна детства, 2007)
Экземпляры: (20210908) / Инвентарный номер: 33670 / Цена: 43.70 / Сис.шифр: 84(2=411.2)6 / Авт.знак: К93 / ГРНТИ: 17 / ББК: 84(2=411.2)6